To the young writer : nine writers talk about their craft - Nuwer, Hank. (New York : Franklin Watts, 2002)
Nine writers, including a Hollywood screenwriter, a novelist, and a sportswriter, talk about their craft.
Includes bibliographical references (p. 105-106) and index.
Keywords: Authorship -- Vocational guidance -- Juvenile literature; Authors, American -- 20th century -- Biography -- Juvenile literature; Authorship; Authors, American